INVESTIGATING HOW MANAGERIAL COMMUNICATION INFLUENCES EMPLOYEE MOTIVATION - Iacob Mihaila, Georgiana Zoe; Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2022)
This paper aims to research the motivation of human resources, with a case study at CONEREPET SA PLОIЕȘTI<a title="" href="file:///C:/Users/Ciotoiu/Desktop/ElaG/desktop/Cercetare%20_articole%20Gurgu%202019/CEN%202022/Lucrari%20masteranzi%20-%20MIA,%20An%202/Study%20case%20CONPET%20SA_Iacob%20Mihaila_Gurgu%20E_Lb%20%20Eng.docx#_ftn1">[1], a Romanian crude oil products transport company. In the first part of the work, we dealt with the theoretical aspect of environmental pollution with petroleum products: polluting factors and methods of depollution. Then we presented theoretical aspects of human resource management, so that we can approach a research study in the second part of the paper. Also, we analyzed the CONEREPЕT SA company, and, like the research study, we dealt with the motivation of human resources within the company. We chose this topic due to the experience in the field. We concluded that human resources are primary among those needs and resources available to the organization in carrying out the activity to achieve its objectives and, consequently, it is logical to pay special attention to their management. At the center of all business are the people. All other resources, land, buildings, machinery, equipment, vehicles, or money are only of secondary importance. Business cannot be done without people. Businesses have no other purpose than to serve people’s needs. <a title="" href="file:///C:/Users/Ciotoiu/Desktop/ElaG/desktop/Cercetare%20_articole%20Gurgu%202019/CEN%202022/Lucrari%20masteranzi%20-%20MIA,%20An%202/Study%20case%20CONPET%20SA_Iacob%20Mihaila_Gurgu%20E_Lb%20%20Eng.docx#_ftnref1">[1] We will not divulge the name of the company where we conducted the case study for security reasons of the data and information provided. Thank you for understanding the situation.